THE EVOLUTION OF THE BROAD LOCAL AUTHORITY TOWARDS THE GUIDED AUTONOMY: THE CASE OF INDONESIA’S INTERGOVERNMENTAL RELATIONS (Lex localis - Journal of Local Self-Government, 2025)
This research explores the evolution of Indonesia's intergovernmental power relations, highlighting the shift from broad local authority to guided autonomy. Using a historical institutional approach, the article reveals that the critical juncture of the 1999 reform established extensive local autonomy, undermining the central authority. Asymmetric power relations and the political context triggered subsequent reforms that deterministically led to the 2014 guided autonomy. Unlike normative and functional approaches, which overlook the structures of power relations and political interactions in institutional change, this article concludes that the reciprocal relationship between political context, institutional settings, and actors' strategies determines the evolution of Indonesia’s intergovernmental power relations.